Inertial Diffusivity of Non-Colloidal Particles in Unbounded Suspending Media and Numerical Simulations - Siginer, D (Elsevier B.V., 2021)
Suspensions in industrial manufacturing processes are prevalent across a spectrum of diverse industries adding more emphasis to the fundamental challenge of predicting on a sound basis the rheological properties as well as the constitutive structure of non-colloidal suspensions under forcing. Thus, the raison d’être of the present work, a comprehensive up-to-date review of an important segment of the non-colloidal suspension mechanics covering the inertial diffusivity of non-colloidal particles in suspension in an unbounded Newtonian fluid medium followed by the closely related review of the numerical simulations of unbounded suspensions. The presence of the boundaries introduces extensive complications and the progress made in inertial and shear induced self-diffusivity in bounded Newtonian and viscoelastic suspending media will be covered in an upcoming review article dedicated to this topic. Efforts have not been spared to be thorough in the presentation with commentaries about the successes and failures of each theory and the reasons behind them expounded within the framework of their historical context. The link between different theories and the naturally unfolding succession of theories over time borne out of the necessity for better predictions as well as the challenges in the field at this time are given much emphasis at the expanse of a detailed in-depth account of various theories. For a detailed in-depth exposition, the reader is referred to the extensive reference list. © 2021 Elsevier B.V.